1999
DOI: 10.1159/000015284
|View full text |Cite
|
Sign up to set email alerts
|

The novel contiguous gene syndrome of myotubular myopathy (MTM1), male hypogenitalism and deletion in Xq28:report of the first familial case

Abstract: Hu et al. (1996) and Laporte et al. (1997) recently proposed a novel contiguous gene syndrome of myotubular myopathy, abnormal male genital development and deletion in Xq28. We studied a family where two male infants, both deceased, had myotubular myopathy and intersexual genitalia. Using FISH we detected in the mother a hemizygous deletion including the myotubularin gene MTM1 and F18 (a gene of yet unknown function). DNA studies with STR-markers (short tandem repeats) within and flanking the deleted segment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…In this regard, although the mouse homolog for CXorf6 is not expressed in the adult testis, it is clearly expressed in the adult ovary (3) where SF1 (4,5) and HES3 are also expressed. In addition, premature ovarian failure has been described in a female with heterozygosity for a microdeletion involving CXorf6 (34). Thus, CXorf6 and its possible interaction with SF1 and HES3 may also be relevant to adult ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, although the mouse homolog for CXorf6 is not expressed in the adult testis, it is clearly expressed in the adult ovary (3) where SF1 (4,5) and HES3 are also expressed. In addition, premature ovarian failure has been described in a female with heterozygosity for a microdeletion involving CXorf6 (34). Thus, CXorf6 and its possible interaction with SF1 and HES3 may also be relevant to adult ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…A gene for 46,XY DSD has been postulated around MTM1 for myotubular myopathy on Xq28, on the basis of the finding that genital development is normal in patients with intragenic MTM1 mutations, and invariably abnormal in 6 patients with microdeletions involving MTM1 [10,11,12,13]. The 6 patients consist of 3 sporadic and 3 familial cases, and 5 of them have glandular, penile, or penoscrotal hypospadias and the remaining 1 patient exhibits ambiguous genitalia [10,11,12].…”
Section: Cloning Of a Candidate Gene For 46xy Dsdmentioning
confidence: 99%
“…The 6 patients consist of 3 sporadic and 3 familial cases, and 5 of them have glandular, penile, or penoscrotal hypospadias and the remaining 1 patient exhibits ambiguous genitalia [10,11,12]. These findings suggest that a gene for 46,XY DSD, especially that for hypospadias, resides in the vicinity of MTM1 , and that loss or disruption of the gene results in the development of 46,XY DSD as consequence of a contiguous gene deletion syndrome.…”
Section: Cloning Of a Candidate Gene For 46xy Dsdmentioning
confidence: 99%
“…It is also hypothesized to be implicated in male genital development. Indeed, myopathic individuals with intragenic mutations of MTM1 have normal sexual development, whereas those with microdeletions of MTM1 extending to the CXorf6 locus have abnormal genitalia (8)(9)(10)(11). Subsequent studies have demonstrated that CXorf6 is mutated in 46,XY disorders of sexual development (46,XY DSD): Fukami et al (12) have identified three nonsense mutations in four individuals with 46,XY DSD including micropenis, bifid scrotum, and penoscrotal hypospadias.…”
Section: Introductionmentioning
confidence: 99%